230k views
0 votes
Y=mx+b solve for x plzzz hurrryyyyy

User Bakoyaro
by
4.8k points

1 Answer

5 votes

Answer:

x = (y - b)/mv

Explanation:

Isolate the variable, x. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS.

First, subtract the variable b from both sides of the equation:

y (-b) = mx + b (-b)

y - b = mx

Next, divide m from both sides of the equation. Remember to divide from all terms on the left side:

(y - b)/m = (mx)/m

x = (y - b)/m

x = (y - b)/m is your answer.

~

User CheeseFlavored
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.